Uranium in groundwater and its potential as a natural contaminant in the Cherokee Basin, southeastern Kansas - Onwuagba, Fidelis Chinaemelum (Kansas State University, 2024)
Safe, easily accessible, clean, and potable water is critical for public health. The ingestion of radioactive nuclides such as uranium has been associated with renal and cancer-related issues in humans. Many previous studies have focused on anthropogenic uranium contamination. Here, we examined the potential for natural uranium contamination from water-rock interaction in black shales. After uranium ores, black shales are the second most important uranium source. Immobile uranium can be mobilized and absorbed into groundwater under ideal geochemical circumstances depending on redox status, carbonate speciation, and alkalinity. The sedimentary succession in the Cherokee Basin in southeastern Kansas includes several black shales interbedded with limestones. Gamma-ray logs from oil and gas wells revealed a very high level of radioactivity in the black shales, reaching 740 API (units of gamma-ray radiation) in some areas, suggesting the presence of radioactive uranium in these rocks. We collected and chemically analyzed groundwater samples from domestic wells screened in the Ozark carbonate aquifer to examine whether these units are sources of groundwater uranium contamination. The samples had a pH of 6.27 to 7.96 and alkalinity ranging from 0.6 to 18 mM. Some samples had high sulfate and nitrate (as N) concentrations, up to 373 mg/L and 22 mg/L, respectively. This study also investigated the connection between black shales and uranium concentrations in groundwater and a possible link to cancer incidence in the study area. Uranium levels were generally low; however, we found numerous other redox-sensitive solutes, specifically mercury, manganese, and iron, in concentrations of 0.02 mg/L, 3.3 mg/L, and 11 mg/L, respectively. These are well above the primary or secondary U.S. EPA and WHO standards for drinking water and are known to be directly or indirectly linked to certain types of cancer in humans, including bladder, brain and nervous system, kidney, blood, lung and bronchus, liver, and pancreas cancer. These results have implications for the best practices for household water well owners and target depths for potential water well owners to ensure drinking water quality, consequently reducing the prevalence of cancer associated with the consumption of contaminated groundwater.
Keywords: Uranium and trace metal contamination in groundwater; Cherokee Basin; Environmental geology; Medical geology; Cancer; Grounwater geochemistry